In search of the fibrotic epithelial cell: opportunities for a collaborative network. Issue 2 (15th June 2011) - Jenkins, Gisli; Blanchard, Andrew; Borok, Zea; Bradding, Peter; Ehrhardt, Carsten; Fisher, Andrew; Hirani, Nik; Johnson, Simon; Königshoff, Melanie; Maher, Toby M; Millar, Ann; Parfrey, Helen; et al.
Abstract : Idiopathic pulmonary fibrosis (IPF) is a chronic progressive disease of unknown aetiology. It has a very poor prognosis and no effective treatment. There are two major barriers to the development of novel treatments in IPF: an incomplete understanding of its pathogenesis and the fact that current models of the disease are poorly predictive of therapeutic response. Recent studies suggest an important role for the alveolar epithelium in the pathogenesis of IPF. However, practical limitations associated with isolation and culture of primary alveolar epithelial cells have hampered progress towards further elucidating their role in the pathogenesis of the disease or developing disease models that accurately reflect the epithelial contribution. The practical limitations of primary alveolar epithelial cell culture can be divided into technical, logistical and regulatory hurdles that need to be overcome to ensure rapid progress towards improved treatment for patients with IPF. To develop a strategy to facilitate alveolar epithelial cell harvest, retrieval and sharing between IPF research groups and to determine how these cells contribute to IPF, a workshop was organised to discuss the central issues surrounding epithelial cells in IPF (ECIPF). The central themes discussed in the workshop have been compiled as the proceedings of the ECIPF.